Wear prediction and meshing characteristics for the planetary gear set considering angular misalignment and rotating carrier. (October 2022) - Tian, Hongxu; Han, Hongzheng; Zhao, Zhifang; Han, Chenyi; Ma, Hui
Highlights: Wear model for the planetary gear set considering angular misalignment and rotating carrier is proposed. The three-dimensional wear distribution is calculated in the presence of different meshing times. The load distribution, time-varying mesh stiffness and backlash under the influence of angular misalignment, rotating carrier and wear are investigated. Abstract: This paper focuses on the effect of angular misalignment on wear prediction of the planetary gear set with the rotating carrier, which is more complex than that of the parallel-axis gear due to the position changing of the planet gears. The wear depth is calculated based on the Archard's wear theory, the load distribution is obtained by the three dimensional loaded tooth contact analysis (3D-LTCA) method, and the effect of angular misalignment is considered by introducing the change in meshing clearance between the two engaged tooth flanks. The load distribution, the time-varying mesh stiffness (TVMS) and the backlash of gear pairs are presented under different wear levels. The results show that, with the combined effect of angular misalignment and rotating carrier, the wear depth on both sides of the face width is larger than that in the middle, and the difference is the greatest at the root. Moreover, TVMS is affected not only by the tooth wear, but also by the rotating carrier, and the cycle of TVMS and the backlash is half of that of the carrier rotation.